Kinerja Alat Pemipil dan Pengukuran Susut Pemipilan Jagung - Sri Lestari; Fajar Kurniawan (Politeknik Negeri Lampung., 2021)
At corn post-harvest handling activities, the shelling process is an important activity that needs special attention. One of the mechanical equipment for post-harvest handling of corn is the corn sheller. The purpose of this study was to measure the scattered losses and quality losses in the corn threshing / shelling process and to analyze the performance of the corn thresher / sheller machine. The results showed that the use of corn sheller with a rotating speed of 652 rpm with a tool capacity of 1.08 tonnes / hour resulted in practical scattered losses (TP) was 0.69%, scattered losses 1 (T1) was 1.85%, scattered losses 2 (T2) was 0.21%. and the scattered losses 3 (T3) was 1.46%. From the results of manual bleaching of shelled corn kernels according to the SNI 01-3920-1995 quality criteria regarding the quality of shelled corn (provided that the corn kernels are dried again until the moisture content reaches 14%), while the results of mechanically plucked corn kernels are not suitable with SNI 01-3920-1995 regarding the quality of shelled corn because it has a level of damage to the seeds> 8% due to the high moisture content of the corn kernels.